Outcomes of children and young adults with T‐cell acute lymphoblastic leukemia/lymphoma who present in critical status. Issue 4 (8th January 2022) - Wayne, Nicole J.; Li, Yimei; Chung, Perry; Coffan, Kristin; Rheingold, Susan R.
Abstract: Background: Patients with T‐cell acute lymphoblastic leukemia and lymphoma (T‐ALL/LLy) commonly present with critical features such as hyperleukocytosis and mediastinal mass, which complicates completing a diagnostic and staging workup and prevents clinical trial enrollment. Procedure: Consecutive patients with T‐ALL/LLy from 1999 to 2019 at the Children's Hospital of Philadelphia were analyzed for pediatric intensive care unit (PICU) admission and various high‐risk features as well as clinical trial enrollment and outcome. Results: We identified 153 patients newly diagnosed with T‐ALL/LLy, 53 (35%) required PICU‐level care within 24 hours and 73 (48%) within 7 days. Non‐PICU patients had a significantly higher clinical trial enrollment rate (79.4%) versus PICU patients (56.1%, P = 0.016). Patients who enrolled on a clinical trial had similar relapse risk to those who did not enroll (relapse rate 20% vs 29%, P = 0.523). Nineteen patients were precluded from trial participation. Risk of relapse was increased for patients admitted to the PICU within 24 hours (26% vs 13%, P = 0.048). Forty‐four patients with T‐ALL presented with hyperleukocytosis, of which 30% relapsed versus 14% without ( P = 0.082). Patients who underwent apheresis for hyperleukocytosis were statistically more likely to relapse (47% vs 15%, P = 0.007). Patients with elevated uric acid (20% vs 16%, P = 0.278), mediastinal mass (20% vs 14%, P = 0.501), or required emergent steroids (20% vs 16%, P = 0.626) had a similar relapse risk. A single second relapse patient survived. Conclusions: Almost half of T‐ALL/LLy patients required PICU‐level care at diagnosis, making enrollment on clinical trials challenging, but trial enrollment predicted better outcome. Physicians should balance maintaining eligibility with safety to offer patients all options.